Guerrilla Lovers Changing the World with Revolutionary Compassion. - Antonucci, Vince (Grand Rapids : Baker Publishing Group, 2010)
With engaging true stories, Antonucci inspires readers to wage war on complacency and surprise the people around them with acts of love.
22. Insurgent Integration23. Simple Obedience; Part 4 Victory; 24. Fleas Win; Acknowledgments; Notes; Resources.
Description based upon print version of record.
Keywords: Christian life; Electronic books